Capital Intensity Moderates Corporate Risk and Thin Capitalization of Tax Avoidance - Ambarita, Parlindungan; Nofryanti, Nofryanti; Rosini, Iin (Asian Journal of Social and Humanities, 2023)
This study aims to determine the effect of corporate risk and thin capitalization on tax avoidance by adding capital intensity as a moderating variable. This research uses a sample of 62 companies from the industrial sector that are listed on the Indonesia Stock Exchange from 2019 to 2021. The data used is secondary data in the form of financial reports and annual reports of the sample companies. Hypothesis testing was carried out using a panel data linear regression model with eviews 12 software. The results of this study indicate that Corporate Risk has an effect on Tax Avoidance, Thin Capitalization has an effect on Tax Avoidance, Capital intensity cannot moderate the effect of corporate risk on Tax Avoidance, Capital intensity cannot moderate the effect of Thin Capitalization on Tax Avoidance